Macro-economic determinants, maternal and infant SDG targets in Nigeria: Correlation and predictive modeling - Adegoke, Yetunde Oluranti; Mbonigaba, Josue; George, Gavin (Frontiers in Public Health, 2022)
Abstract Objectives: Unambiguously, Nigeria is off-track in achieving the health-related SDGs, consequentially, this study aligns with Sustainable Development Goal 3 which borders on “good health and well-being for people by ensuring healthy lives and promoting well-being for all at all ages”. This paper examines the combined effect of health expenditure and other key macro-economic factors on health indices such as maternal and infant mortality in Nigeria. In contrary to existing literature, we formulate a model that predicts the level of macro-economic determinants and health expenditure needed to achieve the year 2030 SDG target for maternal and infant mortality in relation to Nigeria. Methodology: The study employs Autoregressive Distributed Lag (ARDL) that accounts for large T models. The study period spans from 1995 to 2020. Results: We find significant negative relationship between the health outcomes and macro-economic determinants namely, household consumption, total health expenditure, gross fixed capital while we get a significant positive relationship between the health outcomes and unemployment. Our findings are further supported by out of sample forecast results suggesting a reduction in unemployment to 1.84 percent and increase in health expenditure, gross fixed capital, household consumption, control of corruption to 1,818.87 billon (naira) , 94.46 billion (naira), 3.2 percent, and -4.2 percent respectively in order to achieve the SDG 2030 health target in Nigeria. Policy Implication: The outcome of this result will give the Nigerian government an1d stake holders deeper understanding about the workings of the macro-economic factors, in respect to health performance and this will position Nigeria and other SSA countries by extension towards achieving the 70 per 100,000 maternal mortality and 25 infant mortalities per 1000 births SDG target by year 2030. The African leaders can as well pass into law the need for improvement in Macro-economic factors for better health in Africa. We also recommend that the Nigerian government should steadily increase health expenditure to reach and move beyond the forecast level for improvement in maternal and infant mortality, given the present low and unimpressive funding towards the health sector in the country.